A New guide for better technical presentations applying proven techniques with modern tools - Woelfle, Robert M. (Institute of electrical and electronics engineers, 1992)
Providing the latest techniques in one easy-to-use source, this practical guide gives readers the background they need to make highly sophisticated technical presentations--written, oral, even computer graphics. It covers the essential ingredients for all effective presentations, including how to reduce preparation cost and time, how to identify types and quality of visual aids, and much more.